Where do entrepreneurs get information? An analysis of twitter-following patterns. (4th May 2018) - Motoyama, Yasuyuki; Goetz, Stephan; Han, Yicheol
Abstract : The question of where entrepreneurs obtain information that inspires them to innovate has largely remained unexplored. In order to identify specific actors and organizations that entrepreneurs interact, we employ a novel approach using Twitter data from entrepreneurs participating in 'One Million Cups' in Kansas City, a weekly meet-up program where more than 100 entrepreneurs gathered to receive and provide feedback. Our approach allows us, first, to identify specific information sources at the level of entrepreneurs, companies, support programs, media, and key individuals. Second, we find that entrepreneurs relied more heavily on local than on national sources. Third, we find that early-stage entrepreneurs tended to follow more Twitter accounts from wider sources, while more advanced entrepreneurs had sources with specific entrepreneurship-focused organizations, programs, and individuals. The analysis of these specific and local sources can help the public sector identify types of organizations to engage and methods to intervene to promote local entrepreneurial activities.